Good night, Oppy! - McGowan, James (Boyds Mills Press, an imprint of Boyd Mills & Kane, 2021)
"Learn all about the Mars Opportunity Rover ('Oppy') in this fictionalized account of the space exploration robot's time on the red planet."--Author's website.